Isolation and identification of IAA-producing rhizobacteria from Robusta coffee plantations in Dak Nong province - Nguyen Duy Phuong; Nguyen Thi Thu Ha; Nguyen Thanh Duc; Le Thanh An; Pham Thi Thuy Van; Dam Thi Thanh Ha; Nguyen Thanh Ha (Vietnam Journal of Science, Technology and Engineering)
This study aimed to isolate and identify indole-3-acetic acid (IAA)-producing microorganisms from the rhizosphere of Robusta coffee plantations in Dak Nong province, Vietnam. A total of 539 microbial strains (319 bacteria, 140 fungi, and 80 actinomycetes) were isolated and screened for IAA production using the Salkowski colourimetric method. Key findings revealed that 32.0% of bacterial isolates and 33.6% of fungal isolates demonstrated IAA production above 1.0 μg/ml, with 9 bacterial strains and 4 fungal strains producing more than 50.0 μg/ml of IAA. In contrast, only 3.8% of actinomycetes showed minimal activity (1.0-10.0 μg/ml). Key findings of this study is the identification of strain DN13_B03, which exhibited the highest IAA production (178 μg/ml), confirmed by High-performance liquid chromatography (HPLC) analysis with a distinct peak matching the standard IAA sample. Based on morphological characteristics (yellowish-white colonies, Gram-positive rod-shaped cells) and 16S rRNA gene sequencing, we identified DN13_B03 as Priestia megaterium. Optimisation studies revealed that maximum IAA production (205 μg/ml) was achieved with 0.5% L-tryptophan, at pH 6.0, within a broad temperature range (25-40°C). The remarkable IAA-producing capability of this indigenous strain presents significant potential for developing region-specific biofertilisers to enhance sustainable coffee cultivation in Vietnam.